1992
DOI: 10.1002/ar.1092340104
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic vessels of the human dental pulp in different conditions

Abstract: The characteristics of the lymphatic vessel endothelial wall have been investigated in human normal and inflamed dental pulps. In normal pulps the endothelial wall is characterized by the presence of micropinocytotic vesicles and intraparietal channels. In the inflamed pulpal tissue, where an increase in interstitial fluid pressure occurs, the distended endothelial wall presents open junctions between endothelial cells and the openings of the intraparietal channels. Moreover the micropinocytotic vesicles disap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…LYMPHATIC VESSELS Recent electron microscopic (Bishop and Malhotra, 1990;Marchetti et al, 1991Marchetti et al, , 1992 and histochemical (Aoyama et al, 1995) investigations have indicated the existence of lymphatic vessels in the pulp. It is thereby reasonable to assume that the pulp is provided by the ordinary route for DCs to migrate into regional lymph nodes, where they can stimulate naYve T-lymphocytes.…”
Section: Lack Of Epithelium and Mast Cellsmentioning
confidence: 99%
“…LYMPHATIC VESSELS Recent electron microscopic (Bishop and Malhotra, 1990;Marchetti et al, 1991Marchetti et al, , 1992 and histochemical (Aoyama et al, 1995) investigations have indicated the existence of lymphatic vessels in the pulp. It is thereby reasonable to assume that the pulp is provided by the ordinary route for DCs to migrate into regional lymph nodes, where they can stimulate naYve T-lymphocytes.…”
Section: Lack Of Epithelium and Mast Cellsmentioning
confidence: 99%
“…As our investigations and those of others ( Fig. 3; Marchetti et al, 1992) demonstrate, the lymph capillaries in the pulp are fixed in the connective tissue by collagen fibrils, which adhere to the plasmalemma of the endothelial cells, thus ensuring that the lymph capillaries remain open despite pressure changes.…”
Section: Discussionmentioning
confidence: 64%
“…The ensuing search for lymphatic vessels in the dental pulp can be traced back to 1882 (Bödecker, 1882) and has repeatedly been the subject of histological examinations with some controversial findings (Frank et al, 1977;Gä ngler and Mönch, 1980;Isokawa, 1960;Noyes, 1927;Riedel et al, 1966). As a result of more recent studies (Bernick, 1977;Bishop and Malhotra, 1990;Marchetti et al, 1991Marchetti et al, ., 1992Matsumoto et al, 1997;Sawa et al, 1998), the existence of a lymphatic system in the pulp has been established, but the exact functioning of lymphatic drainage within the dental pulp remains unclear.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, research on lymph circulation and reflux in the periodontal tissues of sheep (Au et al, 1996), monkeys (Bernick and Grant, 1978), dogs (Tsukamoto, 1998) and humans (Marchetti et al, 1999) has focused on the gingival lymphatic pathway. Furthermore, existence of lymphatic vessels in the periodontal tissues and the dental pulp has been examined in rats (Kuriu, 1984), cats (Bishop and Malhotra, 1990) and humans (Marchetti et al, 1991(Marchetti et al, , 1992; Aoyama et al, 1995). Previously, we histochernically demonstrated the existence of lymphatic vessels in human dental pulp (Matsumoto et al, 1997) using 5'-nucleotidase (5'-Nase)-alkaline phosphatase (ALPase) double staining (Kato and Miyauchi, 1989;Kato et al, 1993).…”
mentioning
confidence: 99%